ANALISIS TINGKAT EFISIENSI BANK SYARIAH INTERNASIONAL PERIODE 2006-2008 (STUDI EMPIRIS PADA 9 BANK) - MARGALENA, FEBRYANI UNTARI (2011)
This study aims to know the comparative efficiency of Islamic banking in three different areas, namely Southeast Asia, the Middle East, and Britain. The data analyzed are the nine banks with the period 2006-2008. Secondary data obtained from the publication of financial statements of each bank. With this method we can obtain a DEA formulation for Islamic banks that have not reached optimal efficiency to become more efficient by reference to their respective bencmark Islamic banks that have efficient. With this method the results obtained in 2006 and 2007, there were two banks did not efficient 100% inefficient banks in the Middle East region and in south east asia. Then in 2008 saw 100% efficiency for all banks (four banks) in the Middle East. In Southeast Asia kawsan an inefficient banks and three banks have reached 100% efficiency in 2006, increased in 2007 and 2008 only one bank is inefficient and three 100% efficient bank. From 2006 to 2008, Islamic banks operating in the UK always achieve 100% efficiency.